A Collaboration Context of Vocational Andragogy for People with Disabilities in Indonesia - Yohannes Marryono Jamun; Bayu Rahmat Setiadi; Apri Nuryanto; Angga Damayanto; Anggi Tias Pratama (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This research focuses on demonstrating the role of tertiary education institutions in developing the vocational abilities of people with disabilities by developing and implementing a vocational andragogy model. The research method uses a mixed technique. The research participants were 30 people with physical disabilities from a local disability organisation. The results showed that tertiary education played a driving role in local disability organisations, which in turn affected other organisations. This strategy can be implemented by fostering vocational andragogy through self-reflection, the design of conceptual practice, sharing experiences and discussion, role-playing-based contextual co-working to solve problems, coaching on the output of discussion, and agreement on implementation. The importance of vocational andragogy is especially evident in its ability to foster a learning climate that is fun, contextual, and effective at helping participants hone their vocational skills independently and in a relevant way.